Question: Hello, I need help please, I need to use a solution from one system of equations in another system

I have this system

eq1 := diff(x(t), t)-(1/6)*(6*x(t)^3*y(t)+(2*y(t)^2-2)*x(t)^2+3*y(t)*(z(t)-2)*x(t)-2*y(t)^2+2)*sqrt(3) = 0;
                         
eq2 := diff(y(t), t)-(1/6)*(y(t)-1)*sqrt(3)*(y(t)+1)*(6*x(t)^2+2*y(t)*x(t)+3*z(t)-2) = 0;
                                    
eq3 := diff(z(t), t)-(1/3)*z(t)*sqrt(3)*(6*y(t)*x(t)^2+2*x(t)*y(t)^2+3*z(t)*y(t)-2*x(t)-3*y(t)) = 0;

I solved it numerically using these ics

ics := x(0) = -0.01, y(0) = .99, z(0) = 0.01

sol1 := dsolve({ics, op(syst)}, {x(t), y(t), z(t)}, type = numeric, output = listprocedure)

I need to use the x(t), y(t), z(t) as follows
  X :=  eval(x(t), sol1)
  Y :=  eval(y(t), sol1)

Z :=  eval(z(t), sol1)

to solve the following system for P(t), Q(t), R(t) numerically 
eq4 := diff(R(t), t)-P(t)*Z-(-2*(-Y^2+2)*X/sqrt(3)+sqrt(3)*(-2*X^2+Z+4/3)*Y)*R(t) = 0;
eq5 := diff(Q(t), t)-(2/3)*R(t)+2*((1/3)*Y+X)*P(t)/sqrt(3)-(-2*(-Y^2+2)*X/sqrt(3)+2*sqrt(3)*(X^2-(1/2)*Z-2/3)*X)*Q(t) = 0;
eq6 := diff(P(t), t)+(1/2)*R(t)+2*sqrt(3)*X*Q(t)+(2*(-Y^2+2)*X/sqrt(3)+sqrt(3)*(-2*X^2+Z+1)*Y)*P(t) = 0;

Any help please? 

Please Wait...